The Portrayal of Philia and Agape in The Film Adaptation of Dewi Lestari’s Story Hanya Isyarat - Miza Rahmatika Aini; Sabrina Septi Wulandari (Universitas Brawijaya, 2022)
Love is an important thing in human life. Greek Mythology is well-known for the concept of love about Eros, Philia, and Agape. The authors analyze the love depicted in the short film adaptation of Dewi Lestari’s story Hanya Isyarat. This film tells about such kind types of Love. Based on the characters of the short film, it is depicted that types of Love. The purpose of this study is to describe the hidden meaning of the contents of the short film Hanya Isyarat by Dewi Lestari. The method of this study used the descriptive qualitative method. The author conducts in-depth observations to obtain results based on what is depicted in the short film. The data of this research was obtained from the dialogues presented by the characters. By having a depth analysis, the researchers found that there are two types of characters of love, including Philia and Agape because the characters are shown that they have only two kinds of love. All of them are about scarification and adoration without any hope of return.